2013
DOI: 10.1242/jcs.132340
|View full text |Cite
|
Sign up to set email alerts
|

Ras activation and symmetry breaking duringDictyosteliumchemotaxis

Abstract: SummaryCentral to chemotaxis is the molecular mechanism by which a shallow spatial gradient of chemoattractant induces symmetry breaking of activated signaling molecules. Previously, we have used Dictyostelium mutants to investigate the minimal requirements for chemotaxis, and identified a basal signaling module providing activation of Ras and F-actin at the leading edge. Here, we show that Ras activation after application of a pipette releasing the chemoattractant cAMP has three phases, each depending on spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 60 publications
(95 reference statements)
3
87
0
Order By: Relevance
“…This would then allow directional migration to last for a limited period before inhibitory signals reach a level to overcome the excitation signals and cause a switch in direction. The existence of such buildup of inhibitory signals may involve either a delay or a slow rate in their generation following protrusion, as was suggested by a transient peak of various activities at the front, such as Ras, upon the stimulation of cell migration (54,55). On 2D surfaces, we would expect similar oscillations around the cell perimeter upon the disassembly of microtubules.…”
Section: Discussionmentioning
confidence: 80%
“…This would then allow directional migration to last for a limited period before inhibitory signals reach a level to overcome the excitation signals and cause a switch in direction. The existence of such buildup of inhibitory signals may involve either a delay or a slow rate in their generation following protrusion, as was suggested by a transient peak of various activities at the front, such as Ras, upon the stimulation of cell migration (54,55). On 2D surfaces, we would expect similar oscillations around the cell perimeter upon the disassembly of microtubules.…”
Section: Discussionmentioning
confidence: 80%
“…Ras activation is an early response of the chemotaxis network and activated Ras localizes in patches at the front of the cell in a static gradient (33,34). Several experiments were also repeated with a downstream directionalsensing marker for phosphatidylinositol 3,4,5-trisphosphate (PIP 3 ), PH-GFP (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…First, it has been shown that in strains deficient in cAMP signaling, such as the car1/3 – and gβ – strains, there is no chemoattractant-mediated Ras activation [53]. In gα2 – cells there is a brief, weak Ras activation [54]. Second, RasC and RasG proteins activate separate downstream pathways (Figure 3): RasC-GTP activates TORC2, whereas RasG-GTP and RasD-GTP interact with and activate PI3K1 and PI3K2 [47,55,56].…”
Section: Chemotactic Network Of Dictyostelium and Leukocytesmentioning
confidence: 99%